Criatividade e brincadeira de faz-de-conta nas concepções de professores da educação infantil - Stelling, Luiz Felipe Pecanha (2007)
The research investigates the creativity and the thick of pretending play in the conceptions of professors of the Infantile Education, by means of interviews, questionnaires and video tapes. The categories inatist, spontaneity and constructivist on creativity had bee found at parts of the speach (interview), in the definitions (questionnaire) and in the actions of the teachers with the children is situation of pretending play (video tape). The results point that some teachers adopt inatists explanations; others emphasize the spontaneity perspective, and another part is based on a constructivist boarding on creativity. Despite this, in the vide tape interactive episodes, we perceive that almost all tend to intervene with the creative process, making in difficult the spontaneous actions and the innovative proposals.